2012
DOI: 10.1093/ntr/nts010
|View full text |Cite
|
Sign up to set email alerts
|

Reimbursing Dentists for Smoking Cessation Treatment: Views From Dental Insurers

Abstract: Introduction: Screening and delivery of evidence-based interventions by dentists is an effective way to reduce tobacco use. However, dental visits remain an underutilized opportunity for the treatment of tobacco dependence. This is, in part, because the current reimbursement structure does not support expansion of dental providers ' role in this arena. The purpose of this study was to interview dental insurers to assess attitudes toward tobacco use treatment in dental practice, pros and cons of offering dental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…Various factors such as inadequate time and resources dedicated to smoking cessation in cancer patients, low provider reimbursement for cessation treatment, a lack of expertise and training prevent clinicians from addressing smoking cessation [Shields, 2015; Warren, 2015; Morgan, 2011; Toll, 2013; Warren, 2013; Shelley, 2012; Frazier, 2001]. Although the provider reimbursement for offering smoking cessation have improved over the past decade largely for the medical settings [McMenamin, 2008], it is still perceived to be low and inadequate especially for providers running a busy practice.…”
Section: Barriers To Delivery Of Treatment In the Clinical Settingmentioning
confidence: 99%
“…Various factors such as inadequate time and resources dedicated to smoking cessation in cancer patients, low provider reimbursement for cessation treatment, a lack of expertise and training prevent clinicians from addressing smoking cessation [Shields, 2015; Warren, 2015; Morgan, 2011; Toll, 2013; Warren, 2013; Shelley, 2012; Frazier, 2001]. Although the provider reimbursement for offering smoking cessation have improved over the past decade largely for the medical settings [McMenamin, 2008], it is still perceived to be low and inadequate especially for providers running a busy practice.…”
Section: Barriers To Delivery Of Treatment In the Clinical Settingmentioning
confidence: 99%
“…The lack of financial reimbursement is often claimed as a barrier by dental professionals for providing cessation treatment. Donna Shelly et al noted that “lack of data on intervention efficacy” is a main reason why tobacco cessation insurance reimbursement increased for medical offices but not dental clinics, even though the relevance of providing tobacco cessation in dental offices was well recognized . Therefore, results from quality measures research evaluations such as this project, can be a valuable contribution toward providing data to inform decision‐makers.…”
Section: Discussionmentioning
confidence: 99%
“…Shelley et al [61] in a study involving 11 American insurance company executives addressed this fact. The study showed that research and interventions for tobacco cessation are appropriate for routine dental practice.…”
Section: Reimbursement Of Dentists For Tobacco Interventionsmentioning
confidence: 99%
“…Important aspects such awareness, attitude, practices, willingness and barriers were evaluated using hand-delivered, self-administered or via electronic contact were searched. Studies were conducted in many different clusters like dental universities [62], dental health professionals [7,9,12,13,17,32,46,48,[50][51][52]55,56,[63][64][65], dental insurance companies [61], students [1 5,21,28,31,32,38,39,45,47,49,51,53,55,66], dental patients who use tobacco [30,67,68] and dental teachers [44].…”
Section: Surveysmentioning
confidence: 99%